PENGEMBANGAN TEORI PEMBENTUKAN PERILAKU KEAGAMAAN - Joko Subando (MAMBA'UL 'ULUM, 2020)
This study aims to develop a theory of the formation of religious behavior which can be used as a tool to analyze patterns of internalization of understanding of religious schools in Indonesia. The development of this theory was built at the Al-Irsyad religious organization on the grounds that this organization has long been established, this organization is able to manifest Al-Irsyad's distinctive religious behavior and can recruit followers among non-Arab communities. This study uses a mixed method approach (quantitative-qualitative). The quantitative approach is used to obtain mathematical equations in the model of religious behavior formation, while the qualitative approach is used to analyze the findings of mathematical equations to make them more meaningful. Al-Irsyad student respondents in Java were 729 students. The technique of collecting data by means of interviews, documentation and questionnaires. Qualitative data were analyzed descriptively qualitative, while quantitative data were analyzed using Confirmatory Factor Analysis (CFA). The results showed that: 1) the process of forming religious behavior is determined by curriculum design, 2) the formation of religious attitudes is determined by the process of forming attitudes which combines the quality of interaction with a comprehensive method and determined by the design of the desired attitude in the curriculum, 3) religious behavior is largely determined by the attitude and design of the desired behavior in the curriculum.